2016
DOI: 10.1161/jaha.116.004797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Implications of 24‐Hour Ambulatory Blood Pressure Monitoring for the Diagnosis of Hypertension in Kenyan Adults: A Population‐Based Study

Abstract: BackgroundThe clinical and epidemiological implications of using ambulatory blood pressure monitoring (ABPM) for the diagnosis of hypertension have not been studied at a population level in sub‐Saharan Africa. We examined the impact of ABPM use among Kenyan adults.Methods and ResultsWe performed a nested case–control study of diagnostic accuracy. We selected an age‐stratified random sample of 1248 adults from the list of residents of the Kilifi Health and Demographic Surveillance System in Kenya. All participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
11
2
Order By: Relevance
“…The long delay could be explained by the cost of the exam and the fact that the medical costs are directly supported by the patients or their families. In a Kenyan study, 27% of the patients who were scheduled for a free ABPM on a population-based study in a rural area did not show up [8]. It was then concluded that the ABPM was not well-accepted in this context.…”
Section: Contribution Of Abpm To the Diagnosis Of Hypertensionmentioning
confidence: 99%
“…The long delay could be explained by the cost of the exam and the fact that the medical costs are directly supported by the patients or their families. In a Kenyan study, 27% of the patients who were scheduled for a free ABPM on a population-based study in a rural area did not show up [8]. It was then concluded that the ABPM was not well-accepted in this context.…”
Section: Contribution Of Abpm To the Diagnosis Of Hypertensionmentioning
confidence: 99%
“…Furthermore, some factors such as age, sex, measurement technique, and types of ABPM were highly associated with HT diagnosis (10)(11)(12). Then, a subgroup analysis by these factors may be useful to guide BP screening strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a raised BP value on CBPM but a normal ABPM or HBPM value and who are not taking antihypertensive drugs are said to have WCH . In a recent community‐based case‐control study in Kenya including 1248 participants, CBPM significantly overestimated the prevalence of hypertension while missing about half of the participants with true hypertension diagnosed by ABPM . Even though WCH is associated with mild cardiovascular risk, studies have failed to demonstrate a benefit of antihypertensive treatment in preventing cardiovascular events in patients with WCH .…”
Section: Advantages Of Out‐of‐office Bp Monitoring Over Cbpmmentioning
confidence: 99%
“…Finally, compared with CBPM, the BP values of ABPM and HBPM are reproducible and better correlate with cardiovascular risk, preclinical target organ damage, and cardiovascular events . Twenty‐four–hour ABPM has the unique role of identifying abnormal nocturnal BP patterns, which is an independent predictor of cardiovascular events …”
Section: Advantages Of Out‐of‐office Bp Monitoring Over Cbpmmentioning
confidence: 99%